2021
DOI: 10.3390/ijerph18126578
|View full text |Cite
|
Sign up to set email alerts
|

Successful Smoking Cessation among Women Smokers Based on Utilizing National Smoking Cessation Service Type in Korea

Abstract: Background: This study aimed to evaluate the successful smoking cessation across different national smoking cessation services. Methods: This study included data that had been previously entered into the integrated information system for smoking cessation services and comprised 144,688 participants after excluding missing data. These clinics provide face-to-face counseling, phone calls, text messages, and e-mail services for six months and nine sessions. Results: The women-only program had the lowest success r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
3
1
Order By: Relevance
“…The smoking cessation rates in our study were 43.3%, 28.6%, and 21.6% at four weeks, 12 weeks, and six months, respectively. The quit rates were relatively high compared to previously reported rates of 36% at four weeks in female smokers 19 and 12.2% at six months in female smokers. 20 The previous study 20 provided a smoking cessation program that included telephonic counseling and supportive ambassadors.…”
Section: Discussioncontrasting
confidence: 65%
“…The smoking cessation rates in our study were 43.3%, 28.6%, and 21.6% at four weeks, 12 weeks, and six months, respectively. The quit rates were relatively high compared to previously reported rates of 36% at four weeks in female smokers 19 and 12.2% at six months in female smokers. 20 The previous study 20 provided a smoking cessation program that included telephonic counseling and supportive ambassadors.…”
Section: Discussioncontrasting
confidence: 65%
“…This study determined the effects of a ve-day residential smoking cessation program for female heavy smokers. Smoking cessation success rate in female smokers, as reported by South Korea's Smoking Cessation Support Service, was 33.5% after six months at smoking cessation clinics at public health centers and 11.5% after six months of smoking support service for women [23]. For this study's participants, success rate for smoking cessation at six months was 43.7%, the highest among smoking cessation support services for female smokers in South Korea.…”
Section: Discussionmentioning
confidence: 61%
“…Recent studies have reported that women in call centers have a higher prevalence of smoking, ranging from 20 to 37% [3,4]. However, owing to the negative cultural and social atmosphere surrounding female smokers in South Korea, these rates may be underreported [5][6][7]. Despite this negative cultural and social atmosphere, the relatively high rate of smoking among female call center workers may be due to various factors such as work environment, job-related stress, and personal benefits from smoking [3,4].…”
Section: Introductionmentioning
confidence: 99%